Neutrophil membrane engineered HucMSC sEVs alleviate cisplatin-induced AKI by enhancing cellular uptake and targeting - Peipei Wu; Yuting Tang; Can Jin; Min Wang; Linli Li; Zhong Liu; Hui Shi; Zixuan Sun; Xiaomei Hou; Wenya Chen; Wenrong Xu; Hui Qian (Journal of Nanobiotechnology, 2022)
Abstract Human umbilical cord mesenchymal stem cells-derived small extracellular vesicles (hucMSC-sEVs) have been demonstrated as a therapeutic agent to prevent and treat cisplatin-induced acute kidney injury (AKI). However, hucMSC-sEVs still face many problems and challenges in the repair and treatment of tissue injury, including short circulation time, insufficient targeting, and low therapeutic efficacy. Therefore, we constructed engineered hybrid vesicles fused with nanovesicles derived from human neutrophil membranes and hucMSC-sEVs, named neutrophil membrane engineered hucMSC-sEVs (NEX). NEX significantly enhanced the targeting of hucMSC-sEVs to injured kidney tissues, improved the impaired renal function via reducing pro-inflammatory cytokines expression, promoted the proliferation of renal tissue cells, and inhibited renal cell apoptosis in vivo. In addition, NEX enhanced hucMSC-sEVs uptake by NRK52E cells, but inhibited its uptake by RAW264.7 cells. Moreover, administration of NEX reduced cellular oxidative stress and promoted proliferation of NRK52E cells treated with cisplatin in vitro. In summary, our findings indicate that this design of a universal approach enhances the targeting and therapeutic efficacy of hucMSC-sEVs in kidney tissue regeneration, and provides new evidence promoting its clinical application.